Energetic Particle Showers Over Mars from Comet C/2013 A1 Siding Spring. Issue 10 (27th October 2018) - Sánchez – Cano, Beatriz; Witasse, Olivier; Lester, Mark; Rahmati, Ali; Ambrosi, Richard; Lillis, Robert; Leblanc, François; Blelly, Pierre‐Louis; Costa, Marc; Cowley, Stanley W. H.; Espley, Jared R.; Milan, Stephen E.; et al.
Abstract: This paper is a phenomenological description of multispacecraft observations of energetic particles caused by the close flyby of comet C/2013 A1 Siding Spring with Mars on 19 October 2014. This is the first time that cometary energetic particles have been observed at Mars. The Mars Atmosphere and Volatile EvolutioN (MAVEN)‐solar energetic particle (SEP) and the Mars Odyssey‐High Energy Neutron Detector (HEND) instruments recorded evidence of precipitating particles, which are likely O + pickup ions, during the ~10 hr that Mars was within the region of the comet's coma. O + pickup ions were also detected several hours after, although whether their origin is the comet or space weather is not conclusive. We discuss the possible origin of those particles and also the cause of an additional shower of energetic particles that HEND observed between 22 and 35 hr after the comet's closest approach, which may be related to dust impacts from the comet's dust tail. An O + pickup ion energy flux simulation is performed with representative solar wind and cometary conditions, together with a simulation of their energy deposition profile in the atmosphere of Mars. Results indicate that the O + pickup ion fluxes observed by SEP were deposited in the ionosphere around 105 to 120 km altitude, and they are compared with precomet flyby estimations of cometary pickup ions. The comet's flyby deposited a significant fluence of energetic particles into Mars' upper atmosphere, at a similar level to a large space weather event. Plain Language Summary: Comet Siding Spring is a comet from the Oort cloud (a spherical shell of cometary bodies far beyond the solar system) that made a single flyby through the inner solar system in October 2014. It passed very close to Mars on 19 October 2014, at only one third of the Earth‐Moon distance. This is a unique event as a close encounter of this type with Mars is predicted to occur only once in 100, 000 years. In this work, we analyze data from the Mars Atmosphere and Volatile EvolutioN (MAVEN) and the Mars Odyssey missions in order to understand how the Martian atmosphere reacts to such an unusual external event. This is done through the study of energetic particles from the comet. These particles are important as they constitute an energy input into Mars' atmosphere and are therefore useful for understanding atmospheric evolution and habitability. We have found several O + detections from the comet, while Mars was within the comet environment (during ~10 hr). Also, we discuss several other interesting features that occurred after the closest approach, which could be related to comet dust tail impacts between 22 and 35 hr after the comet's closest approach. In general, the comet deposited into Mars' upper atmosphere a similar level of energy to that of a large space weather storm. Key Points: Both MAVEN and Mars Odyssey saw high‐energy O + ions from comet Siding Spring The O + cometary ions deposited significant energy into the upper atmosphere Some effects may have persisted even after Mars left the outer coma of the comet